Implementation of an asymptomatic bacteriuria assessment protocol for patients discharged from the emergency department - Margaret R. Hitchins; Jeannette L. Bouchard; Christopher W. Ingram; Alison I. Orvin (Cambridge University Press, 2023)
Abstract Objective: We evaluated the impact of an asymptomatic bacteriuria (ASB) assessment protocol on the number of antibiotics prescribed for ASB after discharge from the emergency department (ED). Design: Single-center, before-and-after, retrospective cohort study. Setting: The study was conducted at a large community health system in North Carolina. Patients: Eligible patients were discharged from an ED without an antibiotic prescription and had a positive urine culture result after discharge from May through July 2021 (preimplementation group) and October through December 2021 (postimplementation group). Methods: Patient records were reviewed to determine the number of antibiotic prescriptions for ASB on follow-up call before and after implementation of an ASB assessment protocol. Secondary outcomes included 30-day admissions, 30-day ED visits, 30-day UTI-related encounters, and projected antibiotic days of therapy. Results: The study included 263 patients: 147 in the preimplementation group and 116 in the postimplementation group). There were significantly fewer antibiotic prescriptions for ASB in the postimplementation group (50% vs 8%; P < .0001). There were no differences in the incidence of 30-day admissions (7% vs 8%; P = .9761), 30-day ED visits (14% vs 16%; P = .7805), or 30-day UTI-related encounters (0% vs 0%, NA). Conclusions: Implementation of an ASB assessment protocol for patients discharged from the ED significantly reduced the number of antibiotic prescriptions for ASB on follow-up call without an increase in 30-day admissions, ED visits, or UTI-related encounters.